Seasonal variation of Aeromycoflora of Chhattisgarh Institute of Medical Sciences (CIMS), Bilaspur, C.G. (India) - Luka, Rita Shabnam; Sharma, Kavita; Tiwari, Priti (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> This study was carried out to study the diversity of fungi in hospital environment. Gravity settle plate method was used for the isolation of aeromycoflora. The investigation period for this study was from July 2011 to June 2012. During this investigation total 62 fungal species (571 fungal colonies) belonging to 33 fungal genera were isolated. Various environmental factors: wind, moisture, temperature and air pollution affect and alter the density and frequency of a fungal species in any medium. Furthermore, temperature, water potential, humidity and pH have a critical influence on the growth and survival of fungi. It was observed the concentration of the spores in the air varies from season to season probably due to variation in meteorological parameters.